The other 96%: Can neglected sources of fitness variation offer new insights into adaptation to global change?. (20th December 2016) - Chirgwin, Evatt; Marshall, Dustin J.; Sgrò, Carla M.; Monro, Keyne
Abstract: Mounting research considers whether populations may adapt to global change based on additive genetic variance in fitness. Yet selection acts on phenotypes, not additive genetic variance alone, meaning that persistence and evolutionary potential in the near term, at least, may be influenced by other sources of fitness variation, including nonadditive genetic and maternal environmental effects. The fitness consequences of these effects, and their environmental sensitivity, are largely unknown. Here, applying a quantitative genetic breeding design to an ecologically important marine tubeworm, we examined nonadditive genetic and maternal environmental effects on fitness (larval survival) across three thermal environments. We found that these effects are nontrivial and environment dependent, explaining at least 44% of all parentally derived effects on survival at any temperature and 96% of parental effects at the most stressful temperature. Unlike maternal environmental effects, which manifested at the latter temperature only, nonadditive genetic effects were consistently significant and covaried positively across temperatures (i.e., parental combinations that enhanced survival at one temperature also enhanced survival at elevated temperatures). Thus, while nonadditive genetic and maternal environmental effects have long been neglected because their evolutionary consequences are complex, unpredictable, or seen as transient, we argue that they warrant further attention in a rapidly warming world.